PELATIHAN MENULIS ARTIKEL ILMIAH PARA GURU SEKECAMATAN MOJOAGUNG JOMBANG - Supratno, Haris; Raharjo, Resdianto Permata; Indriyanti, Aries Dwi (ABIDUMASY, 2024)
The purpose of this Community Service activity is to provide knowledge and skills for Jombang teachers which include: (1) techniques for writing scientific articles published in indexed national journals, (2) techniques for writing scientific articles published in indexed international journals, and (3) practice of writing computer-based scientific articles. The specific target to be achieved by this activity is that the teachers in Mojoagung sub-district, Jombang Regency are able to: (1) techniques for writing scientific articles published in indexed national journals, (2) techniques for writing scientific articles published in indexed international journals, and (3) practice writing computer-based scientific articles. The methods used are lectures, questions and answers, assignments, and practice writing scientific articles using a computer. This PKM activity has been carried out with very good and smooth results. The implementation of this PKM was carried out at SMAN Mojoagung, Jombnag, attended by 78 people. Participants felt very happy with this activity because the material was very interesting about the technique of writing scientific articles that are ready to be published in national and international journals.